Representasi Nilai Budaya Jawa Dalam Film Pendek “TUMBAS” (Analisis Semiotika Roland Barthes) - Gabriel Sebastian Novaren; Arvin Hardian; Muhamad Khadafi Firman (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study aims to analyze the representation of Javanese cultural values in the short film Tumbas by Riza Pahlevi using Roland Barthes' semiotic approach. The film was chosen as the object of study because it explicitly showcases the conflict between children and parents regarding the use of the Javanese language in daily life. This research employs a descriptive qualitative method, with data collected through visual observation of scenes, dialogues, costumes, and settings presented throughout the 9-minute-42-second film. The findings reveal that Tumbas represents Javanese cultural values such as unggah-ungguh (etiquette), the importance of speaking local languages, and the authoritative role of parents in educating children. The denotative meaning appears in daily activities, such as children fulfilling tasks like shopping. The connotative meaning is portrayed through the emotional expressions of fear and tension when children are scolded for linguistic mistakes. The film also reflects a myth that proper use of the Javanese language is a measure of politeness and moral behavior in society. The color symbolism of clothing such as Saka’s red shirt indicating courage and inner conflict, or Mbah Warno’s purple attire suggesting authority and symbolic violence is also analyzed. The conclusion is that Tumbas delivers a moral message about the importance of preserving local languages while also critiquing rigid and intimidating methods of cultural transmission. The cultural values in the film are conveyed through a complex system of signs, reflecting the tension between preservation and adaptation in Javanese cultural identity among younger generations.